Staging of intestinal‐ and diffuse‐type gastric cancers with the OLGA and OLGIM staging systems. Issue 10 (6th October 2013) - Cho, S.‐J.; Choi, I. J.; Kook, M.‐C.; Nam, B.‐H.; Kim, C. G.; Lee, J. Y.; Ryu, K. W.; Kim, Y.‐W.
Summary Background Operative link on gastritis assessment (OLGA) and Operative link on gastric intestinal metaplasia assessment (OLGIM) staging systems have been proposed for gastric cancer (GC) risk estimation. Aim To validate the OLGA and OLGIM staging systems in a region with high risk of GC. Methods This retrospective study included 474 GC patients and age‐ and sex‐matched health screening control persons in a cancer centre hospital. We classified gastritis patterns according to the OLGA and OLGIM systems using the histological database that a pathologist prospectively evaluated using the updated Sydney system. GC risk according to the OLGA and OLGIM stages was evaluated using logistic regression analysis. Results More GC patients had OLGA stages III–IV (46.2%) than controls (26.6%, P < 0.001), particularly among patients with intestinal‐type GCs (62.2%) compared with diffuse‐type GCs (30.9%). OLGA stages III and IV were significantly associated with increased risk of GC [odds ratios (ORs), 2.09; P = 0.008 and 2.04; P = 0.014 respectively] in multivariate analysis. The association was more significant for intestinal‐type (ORs, 4.76; P = 0.001 and 4.19; P = 0.002 respectively), but not diffuse‐type GC. OLGIM stages from I to IV were significantly associated with increased risk of both intestinal‐type (ORs, 3.64, 5.15, 7.89 and 13.20 respectively) and diffuse‐type GC (ORs, 1.84, 2.59, 5.08 and 6.32 respectively) with a significantly increasing trend. Conclusion As high OLGA and OLGIM stages are independent risk factors for gastric cancer, the staging systems may be useful for risk assessment in high‐risk regions, especially for intestinal‐type gastric cancer.